Pengembangan E-Comic KEMBARA sebagai Media Pembelajaran Pendidikan Pancasila Kelas IV SD pada Materi Membangun Jati Diri dalam Kebinekaan - Virdha, Nadia; Nurhasanah, Nina; Sari, Yofita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2025)
This research and development aims to produce products E-Comic KEMBARA (Cultural Diversity in the Archipelago) as a learning medium for Pancasila Education for grade IV Elementary School on the material of Building Identity in Diversity. This research and development refers to the Hannafin & Peck development model which consists of 3 stages, including: Needs Analysis, Design, Development and Implementation. At the implementation stage, researchers conducted media feasibility test by involving expert review. The feasibility results 1) Material expert validation obtained score 92%, 2) Media expert validation obtained score 98.66%, 3) Linguistic expert validation obtained score 98%. Validation results by experts show that E-Comic KEMBARA has Excellent qualifications. After that, a trial was carried out on students at SDN Rambutan 03 Pagi with the results 1) One to one get percentage of 96%, 2) Small group get percentage of 98.13%, 3) Fieldtest get percentage of 97.95%. The results of all trials have Very Good qualifications. Based on the results obtained from validation by experts and trials on students, the product E-Comic KEMBARA, which was developed by researchers, is very suitable for use as learning medium for Pancasila education in the material Building Identity in Diversity for fourth grade elementary school.